Mobile fitness application for beginners - Mohamed Imran Mohamed Ariff; Nabil Farhan Roslan; Khairulliza Ahmad Salleh; Masurah Mohamad (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
The present project is motivated by the recognition that the use of mobile fitness application is increasingly popular among sports and exercise participants in recent years. However, an extensive research on mobile fitness application indicates that most of them are not suitable for beginners. Thus, this project paper describes the development process of a mobile fitness application for beginners, who are looking at enhancing their physical fitness level. This mobile fitness application is developed using android studio and java language. Upon the development of this mobile fitness application, a user testing was conducted and analyzed. The result shows that users were satisfied with the applications as most test scores were above average. Based on these results, the usage of this newly developed mobile fitness application can be suggested to be used by beginner exercisers.